Strongheart : wonder dog of the silver screen - Fleming, Candace (Schwartz & Wade Books, 2018)
A German shepherd is transformed from Etzel, a police dog in Berlin, to Strongheart, a silent movie star that will need his best acting skills to prove himself innocent of attacking a girl.